2018
DOI: 10.3389/fnagi.2018.00031
|View full text |Cite
|
Sign up to set email alerts
|

Altered Connectivity of the Anterior Cingulate and the Posterior Superior Temporal Gyrus in a Longitudinal Study of Later-life Depression

Abstract: Patients with later-life depression (LLD) show abnormal gray matter (GM) volume, white matter (WM) integrity and functional connectivity in the anterior cingulate cortex (ACC) and posterior superior temporal gyrus (pSTG), but it remains unclear whether these abnormalities persist over time. We examined whether structural and functional abnormalities in these two regions are present within the same subjects during depressed vs. remitted phases. Sixteen patients with LLD and 30 healthy subjects were studied over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 74 publications
0
11
0
1
Order By: Relevance
“…We identified 32 eligible whole-brain neuroimaging papers comparing LLD patients with HC individuals (Albert, Gau, Taylor, & Newhouse, 2017;Bobb et al, 2012;Bricenõ et al, 2015;Byun et al, 2016;Chen et al, 2012;De Asis et al, 2001;Dombrovski et al, 2013;Dumas & Newhouse, 2015;Fang et al, 2015;Guo et al, 2013;Harada et al, 2018Harada et al, , 2016Hou, Sui, Song, & Yuan, 2016;C. M. Huang et al, 2019;Hwang et al, 2010;Lee, Liu, Wai, Ko, & Lee, 2013;Li et al, 2020;Liu et al, 2012;Mah, Williams, Leung, Freel, & Pollock, 2011;Oudega et al, 2014;Rao et al, 2015;Respino et al, 2019;Ribeiz et al, 2013;Smith, Kramer, et al, 2009;Takami, Okamoto, Yamashita, Okada, & Yamawaki, 2007;Wang et al, 2008;Weisenbach et al, 2014;Wong et al, 2016;Xie et al, 2012;Yuan, Zhu, et al, 2008;Yue, Jia, Hou, Zang, & Yuan, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 32 eligible whole-brain neuroimaging papers comparing LLD patients with HC individuals (Albert, Gau, Taylor, & Newhouse, 2017;Bobb et al, 2012;Bricenõ et al, 2015;Byun et al, 2016;Chen et al, 2012;De Asis et al, 2001;Dombrovski et al, 2013;Dumas & Newhouse, 2015;Fang et al, 2015;Guo et al, 2013;Harada et al, 2018Harada et al, , 2016Hou, Sui, Song, & Yuan, 2016;C. M. Huang et al, 2019;Hwang et al, 2010;Lee, Liu, Wai, Ko, & Lee, 2013;Li et al, 2020;Liu et al, 2012;Mah, Williams, Leung, Freel, & Pollock, 2011;Oudega et al, 2014;Rao et al, 2015;Respino et al, 2019;Ribeiz et al, 2013;Smith, Kramer, et al, 2009;Takami, Okamoto, Yamashita, Okada, & Yamawaki, 2007;Wang et al, 2008;Weisenbach et al, 2014;Wong et al, 2016;Xie et al, 2012;Yuan, Zhu, et al, 2008;Yue, Jia, Hou, Zang, & Yuan, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…M. Huang et al, 2019;Hwang et al, 2010;Lee, Liu, Wai, Ko, & Lee, 2013;Li et al, 2020;Liu et al, 2012;Mah, Williams, Leung, Freel, & Pollock, 2011;Oudega et al, 2014;Rao et al, 2015;Respino et al, 2019;Ribeiz et al, 2013;Smith, Kramer, et al, 2009;Takami, Okamoto, Yamashita, Okada, & Yamawaki, 2007;Wang et al, 2008;Weisenbach et al, 2014;Wong et al, 2016;Xie et al, 2012;Yuan, Zhu, et al, 2008;Yue, Jia, Hou, Zang, & Yuan, 2015). Among these four groups of papers had (partially) overlapping samples, including (Bricenõ et al, 2015;Rao et al, 2015;Weisenbach et al, 2014), (Chen et al, 2012;Guo et al, 2013;Liu et al, 2012), (Harada et al, 2018(Harada et al, , 2016, and Yuan, Zhu, et al, 2008). The data from these papers was merged, yielding 26 independent study populations with 674 LLD and 568 HC participants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies connected one or two corticolimbic [posterior cingulate In the first study, individuals with LLD showed a lower FA and higher radial diffusivity (RD) in the tracts connecting the PCC/Pcun with the dACC, but no differences in the tracts connecting the PCC/PCun with the thalamus (Yin et al, 2016a). In the second study, both individuals with current and remitted LLD had a higher MD, RD, AD but no difference in FA compared to the HC group in the tract connecting l-ACC to pSTG (Harada et al, 2018). Finally, a corticolimbic tract study connecting bilateral uncinate fasciculus tracts and bilateral cingulum tracts, revealed a loss of white matter integrity in the right uncinate fasciculus and bilateral cingulum tracts in individuals with LLD (Charlton et al, 2014).…”
Section: Dwi Studies Using Tractographymentioning
confidence: 92%
“…One study used a pairwise BOLD signal average correlation comparison of 87 regions in currently depressed LLD (Tadayonnejad et al, 2014) and found decreased FC in individuals with LLD compared to the HC group in frontalexecutive (i.e., nucleus accumbens) and corticolimbic regions (i.e., rostral anterior cingulate cortex, superior frontal, and middle orbitofrontal gyri). Harada et al (2018) used a Pearson's correlation coefficient score between anterior cingulate cortex (ACC) and posterior superior temporal gyrus (pSTG). The LLD individuals with current depression showed no difference compared to the HC group, however individuals with remitted LLD showed lower functional connectivity compared to the HC group (Table 5).…”
Section: Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation